Global burden and attributable risk factors of inflammatory cardiomyopathy and myocarditis from 1990 to 2019 - Guilan Wu; Wenlin Xu; Shuyi Wu; Chengfu Guan; Jinhua Zhang (Archives of Public Health)
Abstract Background Our understanding of the global burden distribution of inflammatory cardiomyopathy and myocarditis is very limited. Objective To comprehensively assess the global burden distribution and attributable risk factors of inflammatory cardiomyopathy and myocarditis from 1990 to 2019. Methods We extracted the data on death, disability-adjusted life years (DALY), and age-standardized rate (ASR) of inflammatory cardiomyopathy and myocarditis from the 2019 Global Burden of Disease (GBD) study, including the comprehensive data and the data classified by age/sex. Evaluate the epidemic trend by calculating the estimated annual percentage change (EAPC) of the above variables. This paper discusses the spatial differences from four aspects: global, five socio-demographic index regions, 21 GBD regions, and 204 countries and regions. We also estimated the risk factors attributable to inflammatory cardiomyopathy and myocarditis-related deaths. Results In 2019, the global death toll from inflammatory cardiomyopathy and myocarditis was 340,349, and the age-standardized mortality rate (ASDR) was 4.40/100,000, of which the elderly and men were the majority. Although ASR has decreased in developed areas, inflammatory cardiomyopathy and myocarditis are still important health problems in those relatively underdeveloped areas. Similar DALYs burden pattern of inflammatory cardiomyopathy and myocarditis was also observed during the study period. Globally, among men over 60 and women over 65, the proportion of deaths caused by high systolic blood pressure in 2019 was higher than that in 1990. Conclusions Inflammatory cardiomyopathy and myocarditis are still important global public health problems. The changing pattern of the burden of inflammatory cardiomyopathy and myocarditis varies with location, age, and sex, so it is essential to improve resource allocation to formulate more effective and targeted prevention strategies. In addition, the control of blood pressure should be emphasized.